2016
DOI: 10.1177/0194599816642436
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Biomarkers for HPV‐Negative Head and Neck Cancer Identified via Gene Expression Barcode Analysis

Abstract: Our analysis of public genomic data shows promise in identifying biomarkers that may allow clinicians to make more accurate survival predictions. Spectrin is a strong candidate for further biomarker testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…As yet, only few prognostic biomarkers have been investigated in this patient cohort. For example, in silico analysis of expression data deposited in the Gene Expression Omnibus (GEO) identified spectrin, a cytoskleton protein, as a promising new biomarker [ 48 ]. Expression of the tyrosine kinase c-MET has been shown to be prognostic in oral squamous cell cancer, which is in general not associated with HPV-infection [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…As yet, only few prognostic biomarkers have been investigated in this patient cohort. For example, in silico analysis of expression data deposited in the Gene Expression Omnibus (GEO) identified spectrin, a cytoskleton protein, as a promising new biomarker [ 48 ]. Expression of the tyrosine kinase c-MET has been shown to be prognostic in oral squamous cell cancer, which is in general not associated with HPV-infection [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mutation of SPTBN1 is closely related to the occurrence of OPSCC 103 , but the specific molecular mechanism of this change is not clear. Another HPV-negative study of OPSCC demonstrated that spectrins are significantly related to poor prognosis 104 . Collectively, these studies increase the possibility that SPTBN1 is a useful biomarker in OPSCC, but further research is required to clarify this suggestion.…”
Section: βIi Spectrin In Head and Neck Diseasementioning
confidence: 99%
“…Besides, spectrin family was the most detected and identified in cells transfected with UNC5B truncates. In view of the reports of spectrin in impacting tumour development and aggressiveness, [44][45][46][47] the binding of spectrin family to the intracellular domain of UNC5B was also considered to be closely related to the metastasis of BC cells.…”
Section: Discussionmentioning
confidence: 99%